2017
DOI: 10.1016/j.neuroscience.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mice with increased astrocyte expression of CCL2 show altered behavioral effects of alcohol

Abstract: Emerging research provides strong evidence that activation of CNS glial cells occurs in neurological diseases and brain injury and results in elevated production of neuroimmune factors. These factors can contribute to pathophysiological processes that lead to altered CNS function. Recently, studies have also shown that both acute and chronic alcohol consumption can produce activation of CNS glial cells and the production of neuroimmune factors, particularly the chemokine CCL2. The consequences of alcohol-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 79 publications
3
28
0
Order By: Relevance
“…First of all, these results indicated that, although they drink more ethanol overall, female C57BL/6J mice develop escalated EtOH drinking with CIE exposure to an equal degree as males. This is consistent with our previous findings (Bray et al, 2017) as well as others (Bergeson et al, 2016; Crabbe et al, 2012). Another recent study showed escalated EtOH drinking in male C57BL/6J mice, but not in females (Jury et al, 2016); however these results were based on 24hr EtOH drinking as opposed to the limited access model most commonly associated with CIE models.…”
Section: Discussionsupporting
confidence: 94%
“…First of all, these results indicated that, although they drink more ethanol overall, female C57BL/6J mice develop escalated EtOH drinking with CIE exposure to an equal degree as males. This is consistent with our previous findings (Bray et al, 2017) as well as others (Bergeson et al, 2016; Crabbe et al, 2012). Another recent study showed escalated EtOH drinking in male C57BL/6J mice, but not in females (Jury et al, 2016); however these results were based on 24hr EtOH drinking as opposed to the limited access model most commonly associated with CIE models.…”
Section: Discussionsupporting
confidence: 94%
“…Based on these studies, silibinin potentially acts on multiple targets to inhibit AD pathologies. However, the effects of In the present study, learning and memory deficits were assessed using the Y-maze test, novel object recognition test and Morris water maze test, which are widely used methods to investigate the behaviors of mice [17][18][19][20]. The contents of soluble and insoluble Aβ and Aβ plaques are increased in 6-month-old APP/PS1 mice, comparable to patients with AD [21,22].…”
Section: Discussionmentioning
confidence: 86%
“…In the forced swim test, EtOH and H 2 O mice showed no differences in immobility duration or latency to immobility in the forced swim test after eight weeks intermittent EtOH drinking. Others have also reported no differences in first swim test immobility between controls and EtOH mice after chronic intermittent EtOH vapor or ip EtOH injections at various withdrawal time points (Ribeiro-Carvalho et al 2011, Bray et al 2017, Maldonado-Devincci et al 2016. There has been a resurgence in behavioral interpretation of the rodent forced swim test; besides anti-depressive-like behavior, immobility can also be interpreted as stress coping behavior, especially during repeated trials (Commons et al 2017, Molendijk andDe Kloet 2019).…”
Section: Stress Phenotypes During Acute Withdrawal From Etohmentioning
confidence: 99%